Study Of Field Performance Of Fava Bean Genetic Combinations And Their Crossbreeds Under The Influence Of Arginine Spraying (International Journal of Environmental Sciences, 2025)
This study was conducted during the agricultural seasons 2022/2023 and 2023/2024 atAl-zaffarniya research station of the Department of horticulture, with the aim of estimating the genetic dimension of thirteen varieties of peas and evaluating the productive performance of their individual hybrids under the influence of spraying with arginine acid at two concentrations (0 and 250 mg L−1). SSR techniques using 4 initiators and RAPD initiators (8) were used to determine genetic variability, and the analysis resulted in the selection of six varieties with the most genetically divergent and the lowest content of tannin and vicinecontents. A half-crossing program was implemented to produce 15 first-generation (F2) hybrids, and the hybrids and parents were compared in the second season according to a split-plot design within a randomized complete block design (RCBD) with three replicates.The results revealed that parent No. 2 was superior in the number of pods (33.91 pods/plant-¹), while parent No. 3 recorded the highest values for pod weight (51.34 g), number of seeds per pod (9.18 seeds), weight of 100 seeds (144.86 g), and yield per plant (1659.37 g), the highest total yield of (109.90) tons ha-¹. At the hybrid level, the hybrid (4×1) was superior in the weight of 100 seeds (179.08 g), and the hybrid (4×3) in the number of seeds per pod (9.42 seeds), weight of 100 seeds (54.54 g), and yield per plant (1817.53 g/plant-¹), the highest total yield of (133.98) tons ha-¹. The hybrid (5×4) recorded the highest number of pods (34.80 pods/plant-¹). The results showed that spraying with arginine at a concentration of 250 mg L-¹ significantly affected all studied traits except tannin. This treatment achieved the highest averages of: pod weight (42.30 g), number of pods (35.29 pods/plant-¹), number of seeds per pod (7.89 seeds/pod-¹), weight of 100 seeds (158.83 g), yield per plant (1494.33 g/plant-¹), and total yield (99.51) tons ha-¹